Enhancing Cement Mortar Performance with Cornstalk Ash and Graphene Quantum Dots - Lokharn, Hanrob; Hamcumpai, Kantipok; Chindasiriphan, Pattharaphon; Jongvivatsakul, Pitcha; Likitlersuang, Suched (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 30, 2025)
The objective of this study was to investigate the effect of incorporating cornstalk ash and graphene quantum dots (GQDs) into cement mortar, examining properties such as flowability, compressive strength, flexural strength and porosity. Additionally, an assessment was conducted on total embodied carbon dioxide emissions. Cornstalk ash was utilized as a partial replacement for cement at 20% by weight of the cement. Additionally, GQDs were incorporated into the mixture at proportions of 0.3%, 0.6%, 0.9%, and 1.2% by weight of the binder. The results exhibit that the addition of 0.3% GQDs improved mechanical performance of compared cement mortar to control mixture, enhancing both compressive and flexural strength by 42% and 50%, respectively. Regarding total embodied carbon dioxide emissions, the eco-strength efficiency of 0.3% GQDs reached up to 81% compared to the control mixture. The addition of 0.3% GQDs demonstrates the suitable balance between mechanical properties and environmental impact.